PHYSIOLOGICAL ASSESSMENT OF THE FUNCTIONAL STATE OF ORGANISM OF WORKERS OF THE ROLLING PRODUCTION IN THE COURSE OF EMPLOYMENT - Тулеген Нургалиевич Хамитов (Медицина в Кузбассе)
The purpose of the work – the work is devoted to the physiological assessment of the functional state of organism of workers of the rolling production in the course of employment, depending on occupational category.